PENGEMBANGAN LKS BERBASIS PROJECT BASED LEARNING BERBANTUAN LIVEWORKSHEET UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP NEGERI 1 GIDO - Waruwu, Juli Antonius; Mendrofa, Netti Kariani; Mendrofa, Ratna Natalia; Telaumbanua, Yakin Niat (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2025)
Mathematical problem solving skills are one of the important competencies that students must possess. However, in reality, many students still experience difficulties in understanding problems, designing solution strategies, and communicating their results. Therefore, innovative and interactive teaching materials are needed to help students develop these skills. This study aims to determine the validity, practicality, and effectiveness of Student Worksheets (SW) based on Project-Based Learning assisted by Liveworksheet on integer material in grade VII of SMP Negeri 1 Gido. This type of research is research and development (Research and Development). The development model used is ADDIE, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects are students in class VII-B at SMP Negeri 1 Gido. The research instruments include expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The validation results indicate that the SWL falls into the highly valid category with an average score of 95%. The test showed that the Students' worksheet was categorized as practical, with an average response score from teachers and students of 95%. Meanwhile, the effectiveness of the student worksheet was reflected in the average score of students' mathematical problem-solving ability tests, which was 81, with a classical mastery level of 93.75%. Thus, the students' worksheet based on Project-Based Learning assisted by Liveworksheet is declared valid, practical, and effective for improving the mathematical problem solving abilities of seventh-grade students at SMP Negeri 1 Gido.